OP0086 THE DEGREE OF BONE MARROW EDEMA AS DETECTED BY MAGNETIC RESONANCE IMAGING IN THE SACROILIAC JOINTS AND THE SPINE SUSPICIOUS OF AXIAL SPONDYLOARTHRITIS IN THE GENERAL POPULATION IS ASSOCIATED WITH DIFFERENT FACTORS. (2nd June 2020) - Baraliakos, X.; Richter, A.; Feldmann, D.; Ott, A.; Buelow, R.; Schmidt, C.; Braun, J.
Abstract : Background: Taking advantage of a large population-based study we have recently reported that the frequency of bone marrow edema (BME) and fatty lesions (FL) in the sacroiliac joints (SIJ) and the spine of individuals <45 years detected by magnetic resonance imaging (MRI) suggestive of axial spondyloathritis (axSpA) is higher than expected. Objectives: To identify and compare factors associated with the extension of MRI lesions in the spine and the SIJ in the general population. Methods: All available spinal- (sagittal T1/T2 sequences) and SIJ- (semicoronal STIR sequences) MRIs were evaluated by two trained readers blinded to clinical data. BME (SIJ and spine) suggestive of axSpA were recorded. The extension of BME was quantified using the Berlin MRI score. Discrepancies were resolved by consensus. Degenerative lesions of the Modic type were excluded. The association of age (increase per decade), sex, HLA-B27 and hsCRP positivity, smoking (ever smoker vs. no smoker), spinal pain (yes vs. no in last 3 months), body mass index (BMI) categories (WHO definition), physically demanding job, and giving birth within the last 12 month with the severity of BME were examined. Associations between clinical factors and the Berlin MRI score were analyzed by negative binomial regression models resulting in incidence rate ratios (IRRs). Results: MRIs of 793 volunteers from the general population, mean age 37.3±6.3 years, 49.4% male, 8.9% HLA B27+, 7% CRP-positive, 56.9% with back pain in the last 3 months (28.8% with back pain NRS ≥4/10), 35.7% reported physically heavy work, 55% with BMI > 25 kg/m 2, 16.2% current smokers, and 5% of females with pregnancy in the last year before MRI examination, were evaluated. For BME on SIJ-MRIs, significant associations (IRR, 95% confidence level) were found for pregnancy in the last year (3.82, 1.17-14.24), HLA-B27+ (2.42, 1.33-4.55), BMI (25-30 vs. <25; 2.09 (1.33-3.31)) and presence of back pain in the last 3 months (1.54, 1.02-2.33). For BME on spinal MRIs, significant associations were found for age per decade increase (1.45, 1.10-1.91) and physically demanding work (1.45, 1.04-2.00), while HLA-B27+ (1.32, 0.79-2.24), BMI (>30: 0.84, 0.53-1.32 (<25 reference)) and back pain in the last 3 months (1.29, 0.95-1.77) showed no association. Overall, spinal BME was more frequent than SIJ BME in the participants working at a desktop (61.5% vs. 54.4%), while smokers (66.9% vs. 63.8%) and participants with back pain in the last 3 months (62.5% vs. 56.9%) had more often SIJ BME than spinal BME, respectively. Conclusion: In this population-based study, individuals aged <45 years, HLA-B27+, women with pregnancy in the last year and presence of back pain were associated with the extent of BME in the SIJ, while age and physically demanding work were associated with the extent of BME in the spine. These data support the hypothesis of a mechanic origin of BME in the general population aged <45 years, while HLA B27 is a severity but not a susceptibility factor for BME in the SIJ. Acknowledgments: n/a Disclosure of Interests: Xenofon Baraliakos Grant/research support from: Grant/research support from: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Consultant of: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Speakers bureau: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Adrian Richter: None declared, Daniel Feldmann: None declared, Anne Ott: None declared, Robin Buelow: None declared, Carsten Schmidt: None declared, Juergen Braun Grant/research support from: Abbvie (Abbott), Amgen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, Eli Lilly and Company, Medac, MSD (Schering Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi- Aventis, and UCB Pharma, Consultant of: Abbvie (Abbott), Amgen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Eli Lilly and Company, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis, and UCB Pharma, Speakers bureau: Abbvie (Abbott), Amgen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Eli Lilly and Company, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis, and UCB Pharma